Specificity of Design and Action of The Weapon’s Jumpand Recoil Laboratory Test Stand - Łukasz SZMIT (Wojskowa Akademia Techniczna, 2012)
This paper presents the specificity of design and action of the weapon’s jump and recoil laboratory test stand. This laboratory test stand is able to examine the weapon’s jump and recoil of various small arms including technology demonstrators of the new Polish modular rifles (MSBS-5,56) built both in the classic layout and as a bull-pup. Modular rifles and the laboratory test stand were designed and manufactured during a research and development project financially supported by the Polish Ministry of Science and Higher Education from 2007 to 2011.
Keywords: Stanowisko laboratoryjne do badania broni strzeleckiej